1993
DOI: 10.1002/pd.1970130909
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal diagnosis of gall bladder anomalies—report of 17 cases

Abstract: We describe here 17 cases of fetal gall bladder anomalies, detected as early as the 14th week of gestation, out of 10,016 fetal systemic examinations performed by us in the last 6 years (0.15 per cent). In seven cases, agenesis of the fetal gall bladder was detected. The diagnosis was confirmed by post-abortal examination in five cases and in two post-partum. In six other cases, a left-sided gall bladder and in one case, a 'floating' gall bladder were detected at 15 weeks' gestation. In two cases, a septated o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
64
0
3

Year Published

1997
1997
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(70 citation statements)
references
References 7 publications
3
64
0
3
Order By: Relevance
“…Nonvisualization of the fetal gallbladder is rare and occurs in 0.1% to 0.15% of pregnancies (Bronshtein et al, 1993;Blazer et al, 2002), Hertzberg et al (1996) reported a frequency of 7.1%, which may be explained by the small number of patients included between 20 and 24 weeks of gestation (n = 84).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Nonvisualization of the fetal gallbladder is rare and occurs in 0.1% to 0.15% of pregnancies (Bronshtein et al, 1993;Blazer et al, 2002), Hertzberg et al (1996) reported a frequency of 7.1%, which may be explained by the small number of patients included between 20 and 24 weeks of gestation (n = 84).…”
Section: Discussionmentioning
confidence: 99%
“…In three prospective studies, isolated agenesis of the gallbladder explained 12 to 28% of nonvisualization of the gallbladder (Bronshtein et al, 1993;Blazer et al, 2002;Ochshorn et al, 2007). In the present study, amniotic fluid digestive enzymes assays were performed in two of the four cases (amniocentesis not performed in one case and enzymes were not assayed in the other).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nonvisualization of the gallbladder during the second trimester ultrasound should prompt concern for BA 3, 4, 5. Other gallbladder abnormalities can be diagnosed prenatally such as agenesis, left‐sided, septated or bilobed gallbladder 6. The diagnosis of BA is more challenging when the gallbladder is visible.…”
mentioning
confidence: 99%